2011
DOI: 10.1017/s0022112010006051
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-layer thickness effects of the hydrodynamic instability along an impedance wall

Abstract: The Ingard–Myers condition, modelling the effect of an impedance wall under a mean flow by assuming a vanishingly thin boundary layer, is known to lead to an ill-posed problem in time domain. By analysing the stability of a linear-then-constant mean flow over a mass-spring-damper liner in a two-dimensional incompressible limit, we show that the flow is absolutely unstable for h smaller than a critical hc and convectively unstable or stable otherwise. This critical hc is by nature independent of wavelength or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
105
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 30 publications
4
105
0
Order By: Relevance
“…The boundary condition proposed by Rienstra and Darau [12,13] assumes a boundary layer with a small thickness d, a linear velocity profile and a uniform mean density. This two-dimensional boundary condition was derived in the incompressible limit and was devised to provide a good approximation of the hydrodynamic oscillations of the boundary layer (see also [15]).…”
Section: Brambleymentioning
confidence: 99%
See 3 more Smart Citations
“…The boundary condition proposed by Rienstra and Darau [12,13] assumes a boundary layer with a small thickness d, a linear velocity profile and a uniform mean density. This two-dimensional boundary condition was derived in the incompressible limit and was devised to provide a good approximation of the hydrodynamic oscillations of the boundary layer (see also [15]).…”
Section: Brambleymentioning
confidence: 99%
“…This defines a family of boundary conditions characterized by the parameter s. Originally, s was set to zero [12], but subsequently it was suggested to use s ¼ 1=3 to remove the second-order derivative in v [13]. The case s ¼ 1 is also considered here since it is more consistent with the special cases discussed in Section 3.…”
Section: Brambleymentioning
confidence: 99%
See 2 more Smart Citations
“…These two issues are problematic for time-domain simulations, where errors generate perturbations at every frequency, and may result in difficulties with numerical convergence. For frequencydomain computations, however, they are of minor practical importance [23]. It has also been shown that the Myers model fails to result in a single impedance value for wave propagation downstream and upstream in a lined duct when the acoustic boundary layer is not much smaller that the mean flow boundary layer thickness, i.e.…”
Section: A Wem-based Methodology For Computing the Propagation In A Lmentioning
confidence: 99%